Comparative ethnobotanical survey of Pimpinella anisum, Coriandrum sativum, Carum carvi in three zones of Morocco: Therapeutic uses, sources of knowledge, and efficacy against diseases and food purposes - Soussi, Meriem; El Yaagoubi, Wissal; Squalli, Wafae; benjelloun, Meryem; El Ghadraoui, Lahsen (Ethnobotany Research and Applications, 2023)
Background: This study aimed to compile data on the variation of medicinal uses of three medicinal plants (Pimpinella anisum L., Coriandrum sativum L., and Carum carvi L.) among local populations in three Moroccan regions. Methods: Interviews were conducted in seven sites belonging to three regions of Morocco from 2019 to 2020. To analyze recorded data, graphic, descriptive indicators, and multivariate tests were employed. We investigated the responses of participants about therapeutic uses and the factors influencing their responses. Results: In the research zone, interviews were conducted with 600 persons ranging in age from 20 to 60 years who use Pimpinella anisum L., Coriandrum sativum L., and Carum carvi L. for therapeutic purposes. The selected plants were used by participants for food purposes (milk flow), cosmetic interests, and therapeutic roles counting digestive disorders, intestinal spasms, laxatives, dysmenorrhea, bloating, intestinal cramps, and antitussive effects. The majority of people only utilize the plants in their dried form, while tisane, powder, and infusion were the most popular usage forms across all analysed sites. The surveyed sites varied in terms of all studied factors, though. Conclusions: This study could be very helpful in preserving ancestors' knowledge and advancing our understanding of the medicinal plants of Morocco, including the Middle Atlas and the Saiss plain.